Precautionary policing and dispositives of risk in a police force control room in domestic abuse incidents: an ethnography of call handlers, dispatchers and response officers - Black, Alex (Policing and society, 2020)
This article explores the riskwork engaged in by call handlers, dispatchers and response officers in a police force control room in England. We present a novel approach by drawing on the work of Foucault and his concept le dispositif to study riskwork in policing in a post-austerity landscape and to develop the analytical concept of ‘precautionary policing’. Dispositional analysis allows us to focus on social dispositions or inclinations and to demonstrate how these arrangements affect social interaction and organisational behaviour. We draw on data collected via ethnographic fieldwork focusing on domestic abuse incidents in a police force control room in England. The findings focus on: (1) organisational technologies of risk, which guided and surfaced staff actions and decision-making; (2) riskwork to mitigate and manage threats and harm to victims and the public; and (3) riskwork relating to the professional decision-making of individual staff and officers. In addition to bringing the risk tools and artefacts ‘into being’ through their (inter-)actions, for staff, these technologies are a safety net to justify practices. They erode opportunities for officer discretion, particularly in relation to responses to domestic incidents. Therefore, despite policy discussions of the need to reduce officers’ risk aversion and reduce unnecessary bureaucracy, a risk averse culture still pervades. Uncertainty becomes a justification for pre-emptive action by officers and staff before risks become known, and demonstrates a shift to precautionary policing practices which do not follow the blueprints of risk management.